(untitled) (Contemporary Mathematics, 2025)
This paper proposes a real-time energy management strategy for Dedicated Hybrid Transmission (DHT) Hybrid Electric Vehicles based on Equivalent Consumption Minimization Strategy-Dynamic Programming (ECMS-DP), which supports four operating modes: pure electric, boost electric, series and parallel modes. The strategy uses Dynamic Programming (DP) algorithm to solve the Worldwide Harmonized Light Vehicles Test Cycle (WLTC) cycle off-line to obtain the optimal shift line with the objective of energy loss minimization. And the real-time control strategy is based on Adaptive Equivalent Consumption Minimization Strategy (A-ECMS) and the optimal shift line, with minimizing energy loss, engine start/stop times, engine power change and engine speed change as mixed target functions. Then a real-time energy management control system based on ECMS-DP is established. The system utilizes series and parallel Hamiltonian functions to judge the series and parallel modes, and significantly reduces the calibration workload. Through verification in real-vehicle revolving drum test, it has been verified that this strategy can effectively utilize the power battery capacity while maintaining electric balance compared to rule-based strategies such as Rule-Based Threshold Control, and it achieves better fuel economy, with a fuel-saving rate of approximately 5.18%.